The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1108/20426741311328501
|View full text |Cite
|
Sign up to set email alerts
|

Services operations management and humanitarian logistics

Abstract: Purpose -This paper aims to examine the nature of service operations management and its application to the field of humanitarian logistics. The purpose of this paper is to assess developments in the humanitarian logistics (HUMLOG) literature over the last six years and to lay out some opportunities for the HUMLOG academic community in the area of services operations management. Design/methodology/approach -A systematic, quantitative review, consistent with suggestions that the methodological rigor of reviews o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 84 publications
2
83
0
1
Order By: Relevance
“…As "members", LSPs share their resources with HOs, transfer their knowledge, and expand their partners` network. Heaslip [7] acknowledges that business can extend much needed technical expertise to the assisted HO and `fill gaps in humanitarian action.' In return, as Binder and Witte [25] note, LSPs achieve positive branding, improved staff motivation, access to business intelligence, and a desire to 'do good.…”
Section: Logistics Service Providers and Their Roles In Disaster Reliefmentioning
confidence: 99%
See 2 more Smart Citations
“…As "members", LSPs share their resources with HOs, transfer their knowledge, and expand their partners` network. Heaslip [7] acknowledges that business can extend much needed technical expertise to the assisted HO and `fill gaps in humanitarian action.' In return, as Binder and Witte [25] note, LSPs achieve positive branding, improved staff motivation, access to business intelligence, and a desire to 'do good.…”
Section: Logistics Service Providers and Their Roles In Disaster Reliefmentioning
confidence: 99%
“…Recent surveys call for further empirical research to shed lights on currently identified and other roles that LSPs can play in HSC and their consequences [7,24,37]. To the best of our knowledge, very few paper study LSPs in humanitarian contexts empirically [31,32,38].…”
Section: Logistics Service Providers and Their Roles In Disaster Reliefmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most of the discharged chemicals, incinerated at high temperatures, are human carcinogens, which could pose a serious health risk if not treated properly. Thus, wastewater from semiconductor fabrication facilities commonly contains a range of harmful contaminants, such as solvents, arsenic, antimony, acids, alkalis, salts, fine oxide particles, and other pure organic and inorganic compounds [4]. Numerous approaches have been developed to treat the pollution arising from different manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the humanitarian context focuses on standards (mentioned in 47 of the 62 papers) much more than modularity (mentioned in eight papers). All of the papers identified in the review discuss modularity in relation to standards, and the combination is supposed to improve interoperability (e.g., Heaslip, 2013;Kovács and Spens, 2011a and b). Standards are related to improved compatibility (e.g., Beamon and Kotleba, 2006;Perry, 2007), coordination (e.g., Pettit and Beresford, 2009;Bölsche et al, 2013;Kabra and Gamesh, 2015), collaboration (e.g., Overstreet et al, 2011;Schulz and Blecken, 2010), and flexibility (Chandes and Paché, 2010;Overstreet et al, 2011).…”
Section: Modularity and Standards -A Systematic Review Of Hscm Literamentioning
confidence: 99%